Translation, Cross-Cultural Adaptation and Validation of an Amazigh Dialect Version of the DN4 Questionnaire - Elhairech, Dahmane; Kanazy, Saloua; Amghar, Meryem; Bouhrouje, Imane; Banga, Soukina; Elkadmiri, Nadia; Mohammed, Lmejatti (International Journal of Innovative Research in Medical Science, 2022)
Purpose: Neuropathic pain is pain secondary to injury or disease affecting the somatosensory system. The objective of this study was to translate into dialectal Amazigh language and validate the DN4 questionnaire (neuropathic pain in 4 questions), while adapting this questionnaire according to the social and cultural conditions of the Moroccan population. It is a tool to aid in the diagnosis of neuropathic pain established and validated in 2005. It is composed of ten items divided into seven items relating to the questioning and three items relating to the clinical examination. The discriminating threshold value between neuropathic pain and non-neuropathic pain corresponds to the score of four with a sensitivity of 82.9% and a specificity of 89.9%. Patients and methods: the Amazigh version of the DN4 questionnaire was obtained by the translation / back-translation method by a multidisciplinary team. A pre-test was carried out on eighty volunteers to assess the clarity and comprehensibility of the translated items. One hundred and eighty patients were then seen respectively by two other investigators five days apart who scored the DN4 score according to the translated DN4 questionnaire. Reproducibility was assessed by the intraclass correlation coefficient. Results: The comprehensibility of all the items was good, without modification or elimination of any item. The intraclass coefficient was 0.953 for the total score, and between 0.945-0.974 for the separate items showing satisfactory reproducibility. Conclusion: The Amazigh version of the DN4 questionnaire is a simple and valid tool for detecting neuropathic pain. Its applicability to other Amazigh populations is possible, hence the need for further specific studies.